Are nonsteroidal anti-inflammatories effective in the treatment of delayed onset muscle soreness? - Candia-Luján, Ramón (Universidad Autónoma de Tamaulipas, 2014)
Nonsteroidal antiinflammatory drugs (NSAIDs) are wellknown and used in modern medicine. In physical activity, they are used for their antiinflammatory and analgesic actions. The aim of this study was to determine the effectiveness of NSAIDs in the treatment of delayed onset muscle soreness (DOMS). A systematic review was conducted during the months from October to December 2013 in the electronic databases: PubMed, Scopus and SportDiscus, using. An article search strategy was used through the keywords: non steroid antiinflammatory drugs, NSAIDs, delayed onset muscle soreness, and DOMS. Thirty one original studies and one metaanalysis were identified. Twenty six articles were retrieved in full text and five abstracts. After analyzing the studies it was concluded that although the NSAIDs showed some effectiveness in relieving DOMS, there is great diversity in the dose, time of administration used and the general characteristics of the subjects. Therefore, more research is needed to establish their real effectiveness.